Isolation of Pasteurella multocida from chickens, preparation of formalin killed fowl cholera vaccine, and determination of efficacy in experimental chickens - Akhtar, Mahmuda; Rahman, Md. Tanvir; Ara, Mosammat Shamim; Rahman, Marzia; Nazir, K. H. M. Nazmul Hussain; Ahmed, Sultan; Hossen, Md. Liakot; Rahman, Md. Bahanur (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: The objectives of this study were to isolate and identify Pasteurella multocida from fowl cholera (FC) suspected chicken, and to prepare and efficacy determination of formalin killed fowl cholera vaccine using the isolated P. multocida strain. Materials and methods: A total of five suspected dead chickens were collected from Brothers Poultry Farm located at Gazipur district, Bangladesh. The samples were processed and the P. multocida was isolated through conventional bacteriological techniques, were finally confirmed by polymerase chain reaction using P. multocida specific primers targeting cap gene. The P. multocida isolate was used to develop a formalin killed fowl cholera vaccine. The efficacy of the newly prepared vaccine was determined in Starcross-579 chickens (n=30) aging 15 weeks either by injecting 1 mL (group-A; n=10) or 0.5 mL (group-B; n=10) vaccine containing approximately 3.2x10 8 CFU/mL P. multocida organism; 10 birds were kept as unvaccinated control. The sera from the vaccinated and control birds were collected and were subjected for antibody titre determination by enzyme-linked immunosorbent assay (ELISA). Finally the vaccinated birds were challenged using virulent strains of P. multocida to confer the protection against FC. Results: P. multocida could be isolated from both the samples. The formalin killed vaccine prepared from the isolated bacteria was subjected for the determination of antibody titre in chicken, and found that the antibody titres in the birds of group A and group B were 4.513 and 4.07 respectively after primary vaccination, and 4.893 and 4.37 respectively after booster vaccination. Most of the vaccinated birds were found to be survived after challenging with virulent strain of P. multocida. Conclusion: It is concluded that the causal agent of FC (P. multocida) was successfully isolated from FC affected dead chickens. The prepared formalin killed fowl cholera vaccine induces protective immune response and conferred protection against challenge infection caused by the virulent strain of P. multocida. http://dx.doi.org/10.5455/javar.2016.c130